Understanding Iran - Green, Jerrold D. (RAND Corporation, 2009)
A compact, user-friendly handbook for U.S. policymakers interested in understanding the Islamic Republic of Iran. It synthesizes existing analyses on Iran and draws from non-American experts with a different interpretive lens for viewing the seemingly opaque Iranian system. It provides short analytic observations about the processes, institutions, networks, and actors that define Iran's politics, strategy, economic policy, and diplomacy.